Practica de valores - Sailema Yasig, Julio Cesar (2016)
The overall objective of this research was to "diagnose the causes of little practical value to students of the school" Dr. Antonio Ante "by conducting a descriptive research to improve student habits in each educational institution." There is a constant interaction between students and the context in which they operate, these activities help form certain personality traits, and bearing in mind that the student further their education should form the practice of valuesas conscious human being within society. In recent years, technological advances in communications and drastic changes occurring in society against this arises the need to analyze the role played by the family and school in the practice of values for the formation of adolescents. Students must take ownership of certain securities as part of their daily life demonstrating in the surrounding environment with this managed to develop an environment of interaction between educational community and society....